Thickness dependent oxidation in CrCl3: a scanning X-ray photoemission and Kelvin probe microscopies study - Kazim, Shafaq; Parmar, Rahul; Azizinia, Maryam; Amati, Matteo; Rauf, Muhammad; Di Cicco, Andrea; Rezvani, Seyed Javid; Mastrippolito, Dario; Ottaviano, Luca; Klimczuk, Tomasz; Gregoratti, Luca; Gunnella, Roberto (Beilstein Journal of Nanotechnology, 2025)
The modifications in the electronic properties induced by the thickness and size of an individual flake of transition-metal halides on different substrates (silicon oxide or In-doped tin oxide) are of particular technological interest, even more in the case of chromium trihalides (CrX3, X = Cl, Br, and I), whose longer lifetime under ambient conditions is particularly intriguing. By using synchrotron-based scanning photoelectron microscopy with a resolution of 0.1 μm and Kelvin probe force microscopy, we evaluated the surface modification reaction and the surface potential. Our results established the correlations of the two latter properties with the thickness of flakes, observing a natural tendency to preserve their characteristic when the flakes have significantly less thickness. This is in contrast to thicker flakes, which show alteration patterns similar to those observed in bulk-cleaved samples (Kazim, S.; Mastrippolito, D.; Moras, P.; Jugovac, M.; Klimczuk, T.; Ali, M.; Ottaviano, L.; Gunnella, R. Phys. Chem. Chem. Phys.2023, 25, 3806–3814. doi:10.1039/D2CP04586A). This preliminary study investigates interfaces made by dry transfer of CrCl3 flakes in an atmospheric environment. Cl vacancies and the formation of O/CrCl3 are induced, serving as dissociation centers that facilitate the migration of Cl vacancies between the top and bottom surfaces. By manipulating 2D atomic layers via surface oxidation or the introduction of surface vacancies, a novel and versatile approach is unveiled for the development of low-dimensional multifunctional nanodevices.
Keywords: chemical mapping; CrX3; Kelvin probe force microscopy; mechanical exfoliation; scanning photoelectron microscopy (SPEM); two-dimensional material; work function